Volatile compounds and biological activities of essential oil of Gobba pendula Roxb. collected at An Giang province - Phuong, Ngo Thi; Thuy, Dinh Thi Thu; Thao, Do Thi; Huyen, Do Thi Thanh; Hung, Le Ngoc; Anh, Nguyen The; Ha, Le Minh (Vietnam Journal of Science and Technology, 2020)
Twenty-five compounds were identified from the essential oil of Globba pendula Roxb. by gas chromatography–mass spectrometry (GC-MS) with Selinene<d-> (22.09%) as the main component, followed by Ishwarane (6.52%). The essential oil was found to possess moderate NO inhibitory effect with IC50 of 41.68 ±4.51 µg/ml, significant cytotoxic activity against MCF7 and Hep3B cell lines with IC50 of 28.15±1.08 and 35.24±0.06 (µg/ml), respectively. This is the first report on volatile compounds and biological activities of essential oil of Globba pendula Roxb. collected at An Giang province, Vietnam.